Rats did not show evidence of prospective information-seeking: a pilot study - Iwasaki, Sumie; Taniuchi, Tohru (Frontiers in Behavioral Neuroscience, 2023)
Information-seeking behavior often features in research on metacognition in non-human animals; some species seek more information when they do not know the location of a food reward. Rats are known to do this in situations of uncertainty, but it is still unclear if they seek information prospectively for solving a later problem. In this study, we investigated rats’ information-seeking responses in two areas that presented different cognitive challenges (N = 4). In one area, a memory task was presented in which rats could access a cue for a food reward during the information-seeking phase of a trial, but the cue was removed before the subsequent test phase. In the other area, a discrimination task presented a cue that was available in both the information-seeking and the test phases, so that it was not necessary to seek information prospectively. The memory and discrimination test trials were given in quasi-random order (Experiment 1). Rats explored in the memory task area no more than in the discrimination task area during the information-seeking phase, even after extensive training. When they were exposed exclusively to the memory task over multiple sessions (Experiment 2), they developed a strategy of exploring the available object cues. In Experiment 3, rats were found to stay longer in an area, which had an object than in other, less potentially informative areas; they were sensitive to the presence of information. Although these results did not support the existence of prospective information-seeking in rats, they do not necessarily imply that rats lack related abilities. This consideration is due to the constraints of the small sample size and the limited scope of the testing environment. Accumulating not only positive but also negative evidence would further understanding of the factors influencing metacognitive responses in non-human animals.